1978
DOI: 10.1111/j.1365-2621.1978.tb02390.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Formation of Nitrate From Added Nitrite in Model Systems and Cured Meat Products

Abstract: Experiments were designed to determine the effect of the chemical state of myoglobin and presence of ascorbate on the conversion of nitrite to nitrate. In model systems, nitrate was not formed when nitrite was incubated in the presence of either metmyoglobin or ascorbate. However, most of the added nitrite was converted to nitrate when both ascorbate and metmyoglobin were present. It is suggested that ascorbate reduces metmyoglobin to myoglobin, and then, the myoglobin is oxidized simultaneously with nitrite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 9 publications
0
7
1
1
Order By: Relevance
“…Επομένοχ, σε παστεριιομένα προϊόντα από κρέας κοτόπουλου και γαλοπούλας, λόγω της χαμηλής περιεκτικότητας της πρώτης ύλης σε μυοσφαι ρίνη, η μείωση της ποσότητας των νιτρωδών αλάτων που προστίθενται κατά την παραγωγή τους είναι επιβεβλημένη. Μόνο με αυτόν τον τρόπο είναι δυνατή η μείωση της "υπολειμματικής ποσότητας" των νιτριοδιόν και νιτρικών αλάτων και η αποφυγή του κινδύνου σχηματισμού νι-τροζαμινών τόσο in vivo όσο και in vitro 29 .…”
Section: *Bunclassified
“…Επομένοχ, σε παστεριιομένα προϊόντα από κρέας κοτόπουλου και γαλοπούλας, λόγω της χαμηλής περιεκτικότητας της πρώτης ύλης σε μυοσφαι ρίνη, η μείωση της ποσότητας των νιτρωδών αλάτων που προστίθενται κατά την παραγωγή τους είναι επιβεβλημένη. Μόνο με αυτόν τον τρόπο είναι δυνατή η μείωση της "υπολειμματικής ποσότητας" των νιτριοδιόν και νιτρικών αλάτων και η αποφυγή του κινδύνου σχηματισμού νι-τροζαμινών τόσο in vivo όσο και in vitro 29 .…”
Section: *Bunclassified
“…As reported by Fujimaki et al (1975), all added nitrite in cured meat products was transformed to the precursor of cured pigmentation (NO-Mb), gaseous forms (N 2 O and N 2 ), its oxidized form (HNO 3 ), or residuals (NO 2 ). Among the transformations, the majority of nitrite was oxidized to nitrate, which itself could not take part in cured pigmentation (Fujimaki et al, 1975;Lee et al, 1978). Lee et al (1978) noted that a larger amount of nitrate was formed in the presence of ascorbate, and suggested that the ascorbate acted in the metMb reducing system, simultaneously nitrite was oxidized to nitrate as a reaction with ferrous Mb.…”
Section: High Nitrite Levelsmentioning
confidence: 99%
“…Among the transformations, the majority of nitrite was oxidized to nitrate, which itself could not take part in cured pigmentation (Fujimaki et al, 1975;Lee et al, 1978). Lee et al (1978) noted that a larger amount of nitrate was formed in the presence of ascorbate, and suggested that the ascorbate acted in the metMb reducing system, simultaneously nitrite was oxidized to nitrate as a reaction with ferrous Mb. Considering the better reducing activity of pressure treated meat (Cheah and Ledward, 1997), it is likely that more residual nitrite is oxidized to nitrate under pressure treatment.…”
Section: High Nitrite Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This conversion of nitrite into nitrate has been studied previously by Lee et al 23 who reported that both ascorbic acid and metrnyoglobin are necessary. Fox and AckermanZ4 and MohlerZ5 have proposed mechanisms to explain the formation of nitrate from nitrite involving metmyoglobin.…”
Section: Effect Of Other Chemicals On Nitrate and Nitrite Determinationmentioning
confidence: 99%